Pain intensity and salivary α‐amylase activity in patients following mandibular third molar surgery - Wanvipa Surin; Piyanart Chatiketu; Nuntouchaporn Hutachok; Somdet Srichairatanakool; Vuttinun Chatupos (Wiley, 2022)
Abstract Objective We aimed to compare the levels of pain and salivary α‐amylase (SAA) in patients before and after mandibular third molar surgery. Materials and Methods Patients were divided into asymptomatic and symptomatic groups and were then identified by the analgesic drug taken throughout the 2‐week study. The visual analog scale (VAS) was employed to evaluate the severity of pain experienced by a given subject before treatment, when the anesthetic wore off, in the morning, and at night for a period of 1 week. Saliva was collected from the mouth floor of the subjects and the levels of SAA activity were measured at indicated times. Results The levels of postoperative pain were higher than those of pretreatment pain (p < 0.05), but were not necessarily different between the two groups. The pain levels were positively correlated with SAA activities in both groups (p < 0.05). There was no difference between the number of analgesics taken by the two groups and the postoperative complications observed during the study. A significant correlation was observed between the VAS pain scale and SAA activities. Conclusion SAA would be a simple effective biomarker for the objective assessment of pain intensity in patients who have undergone mandibular third molar surgery.